Nursing experience of a patient with Guillain-Barr syndrome after combination therapy with PD-1 inhibitors (PD-1免疫抑制剂联合治疗后出现吉兰-巴雷综合征1例的护理体会) - CHENG Lu (程露); LIU Xiaoxia (刘小霞); QI Zhi (祁智) (中西医结合护理)
This paper summarized the nursing experience of a patient with Guillain-Barr syndrome after combination therapy with PD-1 inhibitors. Keys issues of nursing included care of respiratory muscle paralysis, application of non-invasive ventilator, nasogastric tube feeding and related maintenance, health education on medication and psychological care. (本文总结1例PD-1免疫抑制剂联合治疗后出现吉兰-巴雷综合征的患者的护理经验。护理要点主要包括呼吸肌麻痹的护理及无创呼吸机的使用, 胃管的置入及鼻饲的护理, 用药护理、健康宣教及患者的心理护理。)